Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species - Pinzón-Navarro, Sara V.; Jennings, Debbie; Oberprieler, Rolf G. (Zootaxa, 2017)
This paper presents the results of a three-year collecting and research project on Melanterius weevils in Australia, aimed mainly at discovering new host associations and assessing their fit to the emerging reconstruction of phylogenetic relationships in the large genus Acacia. A revised and extended diagnosis of the genus Melanterius is provided, as well as characters differentiating the genus from related and/or similar Australian genera classified in the tribe Cleogonini. Given the size (79 species) and morphological variation of Melanterius, and to facilitate the assessment of co-evolutionary patterns between the weevils and their hosts, the genus is divided into six tentative species groups characterised by particular morphological traits. New host and locality data are recorded for 23 species, including five species described as new to science, M. abbreviatus sp. n., M. curvistriatus sp. n., M. psittacoides sp. n., M. pungalinae sp. n. and M. tesseymani sp. n. For each species, salient characters and a summary of known host plant species are provided. Melanterius tasmaniensis (Lea, 1909) comb. et stat. n. is raised from a subspecies of Melanteriosoma costatum to species level. All recorded host associations of Melanterius known to us are summarised, including those published, those recorded on label data associated with specimens in the Australian National Insect Collection and those recorded during this study. These host records are differentiated into true host associations (based on specimens reared from seeds), putative associations (based on long series of specimens collected from plants) and coincidental associations (based on single specimens collected from plants). Altogether, Melanterius weevils are recorded from 71 species of Acacia, still a small number in view of the ca. 1000 described species of Acacia, but it is likely that many or most of the other species are also hosts of Melanterius species or of the closely related genus Lybaeba. The pattern of host associations in evidence indicates that most species of Melanterius are not host-specific, developing in the seeds of a number of apparently related Acacia species. Nevertheless, several Melanterius species appear to have the potential to be employed as biocontrol agents if their main hosts become invasive weeds.